Review on cloud service evaluation and selection methods - Alabool, H.M. (2013)
To evaluate and select a Public Cloud Service (PCS) based on Cloud Service Requesters (CSRs) needs and demands a complex software engineering process. Selecting the wrong PCS may turn out to be costly and adversely affect business processes. To address these issues, many Cloud Evaluation and Selection Methods (CESMs) have been proposed by different researchers. Nevertheless, a number of CESMs' studies which have addressed the issue of evaluation and selection of the PCS based on the Quality of Service (QoS) have led to a different conclusion. This paper reviews the current limitations; namely, the strengths and weaknesses of CESMs for the PCS as well as the benefits they bring. The result has shown that current studies of CESMs are limited to certain types of quantifiable criteria, such as cost and performance. Non-quantifiable QoS criteria namely, trust, needs further attention. In addition, it has been identified that the majority of CESMs were not specifically designed for any CS layer; hence, it did not assist the CSP to evaluate their PCS with respect to other providers. Â© 2013 IEEE.